Hyperbaric Oxygen Therapy as a Complementary Treatment in Glioblastoma—A Scoping Review - Alpuim Costa, D (2022)
Glioblastoma (GBM) is the most common and aggressive malignant brain tumor in adults. The mainstay of management for GBM is surgical resection, radiation (RT), and chemotherapy (CT). Even with optimized multimodal treatment, GBM has a high recurrence and poor survival rates ranging from 12 to 24 months in most patients. Recently, relevant advances in understanding GBM pathophysiology have opened new avenues for therapies for recurrent and newly diagnosed diseases. GBM's hypoxic microenvironment has been shown to be highly associated with aggressive biology and resistance to RT and CT. Hyperbaric oxygen therapy (HBOT) may increase anticancer therapy sensitivity by increasing oxygen tension within the hypoxic regions of the neoplastic tissue. Previous data have investigated HBOT in combination with cytostatic compounds, with an improvement of neoplastic tissue oxygenation, inhibition of HIF-1α activity, and a significant reduction in the proliferation of GBM cells. The biological effect of ionizing radiation has been reported to be higher when it is delivered under well-oxygenated rather than anoxic conditions. Several hypoxia-targeting strategies reported that HBOT showed the most significant effect that could potentially improve RT outcomes, with higher response rates and survival and no serious adverse events. However, further prospective and randomized studies are necessary to validate HBOT's effectiveness in the 'real world' GBM clinical practice.